Quality assurance of high education - A. M. Aleksankov; V. E. Mager; L. V. Chernenkaia; A. V. Chernenkii (Открытое образование (Москва))
The article expounds questions concerning Quality assurance of Higher education, related to the entry of Russia into the united European Higher Education Area. The main emphases is focused on the necessity to create the system for Quality assurance of Russian Higher education, which will be harmonized with European systems. Comparing of Russian and European approaches in Quality assurance of Higher education is drawn. Russian system of Quality assurance of Higher education is considered on four levels: State level, level of Higher educational institution, level of society and international level; for each level the main elements of a system are determined. Since the European approach separates the Quality assurance system into two levels, e.g. internal and external, a conversion to comparable levels is being proposed. Characteristics of EURopean ACcredited Engineer (EUR-ACE) Framework Standards are expounded. These Standards have been developed, fi rst of all, for facilitation of the procedure of acceptance of degrees and qualifi cations as well as Quality assurance of Study Programmes in European Higher Education Area. The comparison of requirements of Federal State Educational Standards for Higher education in Russian Federation and EUR-ACE Framework Standards is produced on the example of Masters’ Study programmes in Engineering. The comparison exposed similarities and, at the same time, considerable differences in examined approaches. So, the results of studies are formulated in different “coordinate systems”: according with kinds of activities in Federal State Educational Standards for Higher education, but according to the “cycle” of Engineering activity in EURACE Framework Standards. However, if the task for harmonization of standards (or requirements) could be considered out of just simple coincidence between their structures and/or definitions and terms, than the principle contradictions between European and Russian approaches in Quality assurance will not appear. It means that the ways of harmonization of European and Russian requirements to Study Programmes’ Quality assurance could be found. And the logical part of implementation of international Quality management schemes will be the accreditation of Russian Study programmes in international organizations and networks. In order to ensure the effectiveness of such tasks, it is necessary to develop an appropriate tools, which could help to formalize and systematize procedures of Study Programmes’ Quality assurance with a glance of requirements of European standards. The experience of St. Petersburg Polytechnic University (SPbPU) on Quality assurance of Study Programmes is discussed, in particular: development and appraisal of Technique for monitoring of Study Programmes and of the Model for on-line Quality Assurance of Study Programmes with a glance of requirements of European standards, which have been created in frames of the project TEMPUS EQUASP («On-line (Electronic) Quality Assurance of Study Programmes») with participation of SPbPU. Implementation of proposed tools ensures the integrity and authenticity of information on all aspects of the realization of educational process, fulfi llment of all-European requirements on Study Programmes’ accreditation, harmonization of Russian and European Higher education systems, and, thus, forms the basis for Study Programmes’ accreditation in international organizations and networks. The Model for on-line Quality Assurance of Study Programmes is a powerful tool, which allows to bring the process of Quality Assurance of Study Programmes into accord with European standards and guidelines, to improve quality of Programmes, to increase their transparency and comparability.